2003
DOI: 10.1161/01.cir.0000070540.80780.92
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Catheter-Based Local Intracoronary Vascular Endothelial Growth Factor Gene Transfer in the Prevention of Postangioplasty and In-Stent Restenosis and in the Treatment of Chronic Myocardial Ischemia

Abstract: Background— Catheter-based intracoronary vascular endothelial growth factor (VEGF) gene transfer is a potential treatment for coronary heart disease. However, only limited data are available about local VEGF gene transfer given during angioplasty (PTCA) and stenting. Methods and Results— Patients with coronary heart disease (n=103; Canadian Cardiovascular Society class II to III; mean age, 58±6 years) were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
111
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(112 citation statements)
references
References 30 publications
0
111
0
1
Order By: Relevance
“…DOTMA is a cationic lipid used as a gene delivery liposome (Felgner et al, 1984;Wollenberg et al, 1999;Hedman et al, 2003). The particle size of the complex was significantly reduced by DOTMA addition and settled to 74-114 nm, indicating pDNA compaction (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…DOTMA is a cationic lipid used as a gene delivery liposome (Felgner et al, 1984;Wollenberg et al, 1999;Hedman et al, 2003). The particle size of the complex was significantly reduced by DOTMA addition and settled to 74-114 nm, indicating pDNA compaction (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Most gene therapy clinical trials for CAD were focused on the administration of genes encoding angiogenic growth factors, such as VEGF and FGF4, aiming to promote the development of collateral blood vessels in ischemia-related conditions. Early trials, such as VIVA [53] and KAT [52], suggested a functional improvement in myocardial perfusion and cardiac function in patients with CAD after the administration of either an expression plasmid or an adenoviral vector expressing VEGF-A 165 , respectively. However, subsequent, double-blind, randomized, placebo-controlled studies (EUROINJECT-ONE, NORTHERN) [55,56] failed to demonstrate any improvement in myocardial perfusion.…”
Section: Progress and Challenges In Gene Therapy For Cardiovascular Dmentioning
confidence: 99%
“…One of the main problems with the use of plasmid DNA, is the lack of response with an increasing dosage . The use of this vector, is considered relatively safe, but it has demonstrated in animal models that it can produce fever, inflammation and infarcts in the skeletal muscle and in the myocardium (Hedman et al, 2003). DNA and RNA oligonucleotides potential to be used as decoys, were mentioned over 10 year ago, but their minimum effectiveness in tissues, also discards them for some clinical application (Alexander et al, 2005).…”
Section: Vectors Used For Cardiovascular Gene Therapymentioning
confidence: 99%
“…Likewise the possibility of perform transference of genomic material in vivo, has been made possible exploring this technique as an option to correct the defects present in CVD, under the premise of being a therapy able to correct the underlying defects present in the failing heart. Although the treatment by transference of genetic material still presents many challenges, small clinical tests have already been performed, applying angiogenic factors in ischemic cardiomyopathy (Hedman et al, 2003;Kastrup et al, 2005;Stewart et al, 2006). In relation to other molecular mechanisms of the HF, as it is mentioned below, several of them are in clinical phases in different stages of proximity to a wider clinical setting.…”
Section: Introductionmentioning
confidence: 99%